Maintenance of activities of daily living despite risk from genetic polymorphism in hemodialysis patients under nutritional management who survived an average of 30 years. Issue 1 (December 2015) - Sakamoto, Kaori; Kanno, Yoshihiko; Hiraoka, Mami; Hayashi, Matsuhiko; Kontai, Yoshiko; Kagawa, Yasuo
Abstract Background Only 4 % of hemodialysis (HD) patients survive over 25 years after their initiation of HD even in Japan. To elucidate their clinical characteristics, we investigated their lifestyle and genetic factor. TT genotype of methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism was reported as a high-risk factor for cardiovascular event and poor survival in CKD patients. Method Seventy-eight of Japanese patients receiving HD more than 30 years were enrolled. Their daily lifestyle and activity were evaluated with diet history questionnaires (DHQ), geriatric nutritional risk index (GNRI), and basic activity of daily living (BADL) scores. MTHFR C677T was genotyped by PCR-restriction fragment length polymorphism (RFLP). Results The mean dietary intake of energy was 30.6 ± 9.3 kcal/kg of ideal body weight (IBW), protein 1.1 ± 0.4 g/kg of IBW and their adequacy ratios for Japanese guideline 2007 were 97.7 and 101.9 %, respectively. BADL was 90, and daily activities were highly maintained in patients. The frequency of TT genotype was 26.9 % and it was almost twice as that in the general population. The patients with TT genotype had lower serum folate and higher serum homocysteine than those with the CC or CT genotypes, though there was no significant difference in dietary folate intake among them. Conclusion Although the frequency of TT genotype was higher than healthy population, our patients showed longer survival with high QOL and nutritional status. It is suggested that the proper lifestyle might overcome the genetic risk factors in patients receiving HD.